Perception of the Lexeme 'Europe' by Students: A Psycholinguistic Analysis - Postolova, Iryna; Постолова, Ірина; Tomarieva, Nataliia; Томарєва, Наталія (My University, 2018)
The article analyzes the results of the free associative experiment, which was conducted among first-year students during 2016-2018. According to the frequency of reactions, the authors model the structure of the associative field: nucleus, body and periphery; define the morphological and semantic groups of associations on the word-stimulus ‘Europe’ obtained during the experiment, analyze the syntagmatic and paradigmatic relationships among the reactions, build the structure of the resulting associative field. The responses of respondents are significantly dominated by nouns; occasionally occur adjectives, verbs, adverbs and pronouns; adjectives and adverbs are mostly colored with emotions and estimations. Phrases make a significant group of associations phrases (about one fifth). Among the above mentioned things, toponyms and surnames of well-known political figures are named. Semantically, all associations are divided in general cultural, economic and political, such ones that express aesthetic perception of the word-stimulus, as well as those related to travel and leisure. Special attention in the article is given to emotional coloring of reactions (they are divided in positive, negative and neutral). Thus, the material presented in the work reflects, to a certain extent, the perception of the word-stimulus ‘Europe’ by contemporary student youth. У статті проаналізовано результати вільного асоціативного експерименту, який було проведено серед студентів першого курсу протягом 2016-2018 років. З огляду на частотність реакцій, автори моделюють структуру ассоціативного поля: ядро, тіло та периферію; виділяють морфологічні та семантичні групи асоциацій на слово-стимул “Європа”, отриманих під час експерименту, аналізують синтагматичні та парадигматичні зв’язки між реакціями, вибудовують структуру отриманого асоціативного поля. У відповідях респондентів значно переважають іменники, зрідка зустрічаються прикметники, дієслова, прислівники та займенники, причому прикметники та прислівники здебільшого емоційно та оціночно забарвлені. Значну групу ассоціацій становлять словосполучення (приблизно п’яту частину). Серед іншого були названі топоніми та прізвища відомих політичних фігур. Семантично асоціації поділяються на загальнокультурні, економіко-політичні, ті, що виражають естетичне сприйняття слова-стимулу, а також ті, що повязані з подорожами та відпочинком. Емоційному забарвленню реакцій у статті приділено особливу увагу (вони поділяються на позитивні, негативні та нейтральні). Отже, представлений у роботі матеріал у певній мірі відображає сприйняття лексеми “Європа” сучасної студентською молоддю.
Сприйняття лексеми “Європа” студентами: психолінгвістичний аналіз.
Keywords: psycholinguistics; associative experiment; word-stimulus “Europe”; reaction; perception; психолінгвістика; асоціативний експеримент; слово-стимул “Європа”; реакція; сприйняття